2011
DOI: 10.5194/angeo-29-2327-2011
|View full text |Cite
|
Sign up to set email alerts
|

The Turbopause experiment: atmospheric stability and turbulent structure spanning the turbopause altitude

Abstract: Abstract. Very few sequences of high resolution wind and temperature measurements in the lower thermosphere are available in the literature, which makes it difficult to verify the simulation results of models that would provide better understanding of the complex dynamics of the region. To address this problem the Turbopause experiment used four rockets launched over a period of approximately two hours from Poker Flat Research Range, Alaska (64 • N, 147 • W) on the night of 17-18 February 2009. All four rocket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…The main purpose of the experiment was to study the transition from strong mixing and turbulence to more laminar behavior as visible in chemical trail releases. Results of the wind, temperature, and turbulence measurements were reported by Lehmacher et al (2011), and a mixing event in the mesosphere observed in the sodium layer was studied by Collins et al (2011).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The main purpose of the experiment was to study the transition from strong mixing and turbulence to more laminar behavior as visible in chemical trail releases. Results of the wind, temperature, and turbulence measurements were reported by Lehmacher et al (2011), and a mixing event in the mesosphere observed in the sodium layer was studied by Collins et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…The blue and red rocket profiles are shifted in time and scaled to match the electron densities (see also Fig. 2 in Lehmacher et al, 2011). Background densities are 8 × 10 9 m −3 and layer peak densities are 3 to 4 × 10 10 m −3 , which is low compared to many other Es measurements.…”
Section: Observationsmentioning
confidence: 99%
See 3 more Smart Citations